A strain-rate-dependent modified Cam-Clay model for the simulation of soil/rock compaction. (September 2017) - Cassiani, G.; Brovelli, A.; Hueckel, T.
Abstract: This paper presents a new geomechanical constitutive model that describes the response of deep sediments to increased effective stress, as generated for instance by hydrocarbon or water extraction from the subsurface. The model has the capability of representing the delayed onset of deformation and its continuation after stop of the stress change (creep), and it is based upon the combination of a classical three-dimensional geomechanical model (the Modified Cam Clay Model) and an empirical formulation of the dependence of deformation on the rate of applied stress or resulting strain, originally developed by J.A. de Waal and coworkers in the late 1980s. The advantages of the resulting model, with respect to other formulations, is its solid consistency with geomechanical general theories, its full three-dimensional formulation, and its capability of simulating time-dependent phenomena increasingly observed in practice. Here we present the model formulation and its relationship with existing theories, and we show how the model can reproduce the behavior of consolidated and poorly consolidated sandstones tested in laboratory experiments. Highlights: We have developed a 3D, strain rate-dependent version of the well-known Modified Cam Clay model. The new model is based on the nonstationary flow locus theory and on the rate of plastic strain. The model was successfully used to reproduced laboratory tests. The model can reproduce the delayed onset of compaction and subsidence.